L’uso delle mappe mentali per l’apprendimento della lingua francese - Benzo, Veronica (Edizioni Ca’ Foscari, 2021)
It is easy to teach a good student who shows no difficulty in learning. A greater commitment is necessary however, with a learner who is unable to follow the set pace and pursue the set educational objectives. This paper is the fruit of a collaborative, didactic experience centered on the use of mental maps which has led to excellent results. This tool is often associated with didactics for learners who have specific learning difficulties. We have used mental maps in the organizational stage of learner’s study, for their presentations, in the review stage and for their written French work, increasing both the performance and concentration of university students.